1997
DOI: 10.1006/dbio.1997.8660
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Central Nervous System Lineages ofDrosophila melanogaster

Abstract: In Drosophila, central nervous system (CNS) formation starts with the delamination from the neuroectoderm of about 30 neuroblasts (NBs) per hemisegment. They give rise to approximately 350 neurons and 30 glial cells during embryonic development. Understanding the mechanisms leading to cell fate specification and differentiation in the CNS requires the identification of the NB lineages. The embryonic lineages derived from 17 NBs of the ventral part of the neuroectoderm have previously been described (Bossing et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(137 citation statements)
references
References 45 publications
5
131
0
Order By: Relevance
“…Fng sensitizes the Notch receptor on the anterior LG to stimulation from developing axons bearing the Delta ligand and thereby promotes neuron-to-glial signaling during embryogenesis . Anterior and posterior LG are derived from a common glioblast (Schmidt et al, 1997;Beckervordersandforth et al, 2008), and so, as a consequence of this interplay between neurons and glia, Fng provides a mechanism for the selective expression of Eaat1 in the anterior LG subtype. Thus, Fng promotes the emergence of a functionally distinct glial cell subtype that can take up glutamate and has the potential to modulate neurotransmission at central synapses.…”
Section: Differentiation Of Functionally Distinct Glial Cell Subtypesmentioning
confidence: 99%
“…Fng sensitizes the Notch receptor on the anterior LG to stimulation from developing axons bearing the Delta ligand and thereby promotes neuron-to-glial signaling during embryogenesis . Anterior and posterior LG are derived from a common glioblast (Schmidt et al, 1997;Beckervordersandforth et al, 2008), and so, as a consequence of this interplay between neurons and glia, Fng provides a mechanism for the selective expression of Eaat1 in the anterior LG subtype. Thus, Fng promotes the emergence of a functionally distinct glial cell subtype that can take up glutamate and has the potential to modulate neurotransmission at central synapses.…”
Section: Differentiation Of Functionally Distinct Glial Cell Subtypesmentioning
confidence: 99%
“…Glioblasts, on the other hand, produce pure glial lineages (Bossing et al 1996;Schmid et al 1997;Schmid et al 1999). In some neuroglioblast lineages, the bifurcation between the neuronal and the glial lineages occurs in the primary division to produce a neuronal and a glial precursor (figure 4a; Akiyama-Oda et al 1999; Bernardoni et al 1999).…”
Section: Neurogenesis In Drosophila (A) Neuroblast Formation: Notch Smentioning
confidence: 99%
“…In Drosophila, DiI lineage tracing studies have shown that embryonic neuroblasts produce near invariant lineages, usually containing distinct cell types (Bossing et al 1996;Schmid et al 1997Schmid et al , 1999. Furthermore, progeny are generated in an invariant birth order (Akiyama-Oda et al 1999;Novotny et al 2002;Pearson & Doe 2003).…”
Section: Specification Of Temporal Identitymentioning
confidence: 99%
“…In several representatives of this group of organisms all neuroblasts in the thoracic ganglia are individually identified concerning their position and the lineage which they generate and are well characterized on the molecular level (e.g. Doe 1992; Doe and Technau 1993;Broadus et al 1995;Bossing et al 1996;Schmidt et al 1997; see also the hyper neuroblast map at http://www.neuro.uoregon. edu/doelab/nbintro.html).…”
Section: Introductionmentioning
confidence: 99%